Fatigue impairs kinematics but not kinetics of landing and cutting movements in elite youth female handball players - Schmidt, M.; Nolte, K. F.; Terschluse, B.; Jaitner, T. (ISBS Proceedings Archive (Michigan), 2020)
Lower extremities are the most affected areas of injuries in indoor team handball, especially for female youth player. The mechanics of such injuries are well-known, however little is known about the influence of fatigue injury on risk factors. This study addresses fatigue-induced changes of movements that are associated lower extremity injuries in female youth handball players. Kinematics and kinetic data of 15 elite youth female team handball players were recorded for double- and single-leg landings as well as sidecutting maneuvers before, in the middle of and after a simulated handball specific load protocol. The protocol consisted of exercises typical for handball match activity. RPE was used as measure of fatigability and showed values ranging from 13 to 18 at the end of the treatment. ANOVA revealed fatigue related changes in initial knee flexion angle of the non-dominant leg in all tasks. For the cutting task, significant changes of the initial knee angle of the dominant leg, the initial and maximum hip flexion angle as well as maximum knee flexion angle of the non-dominant leg were observed. Consequently, fatigue players exhibited more extended movement patterns. In summary, the fatiguing protocol caused changes in landing and cutting kinematics of the non-dominant leg predominantly, whereas movement kinetics where not affected.